CDH1/E-cadherin germline mutations in early-onset gastric cancer. Issue 11 (26th June 2006) - Bacani, J T; Soares, M; Zwingerman, R; di Nicola, N; Senz, J; Riddell, R; Huntsman, D G; Gallinger, S
Abstract : Background: Gastric cancer remains a leading cause of cancer deaths worldwide. Genetic factors, including germline mutations in E-cadherin ( CDH1, MIM#192090) in hereditary diffuse gastric cancer (HDGC, MIM#137215), are implicated in this disease. Family studies have reported CDH1 germline mutations in HDGC but the role of CDH1 germline mutations in the general population remains unclear. Aims: To examine the frequency of CDH1 germline mutations in a population-based series of early-onset gastric cancer (EOGC <50 years old). Methods: 211 cases of EOGC were identified in Central-East Ontario region from 1989 to 1993, with archival material and histological confirmation of non-intestinal type gastric cancer available for 81 subjects. Eligible cases were analysed for CDH1 germline mutations by single-strand conformation polymorphism, variants were sequenced, and tumours from cases with functional mutations were stained for E-cadherin (HECD-1) using immunohistochemistry. Results: 1155 (89%) of 1296 polymerase chain reactions amplified successfully. One new germline deletion (nt41delT) was identified in a 30-year-old patient with isolated cell gastric cancer. The overall frequency of germline CDH1 mutations was 1.3% (1/81) for EOGC and 2.8% (1/36) for early-onset isolated cell gastric cancer. Conclusion: This is the first population-based study, in a low-incidence region, of genetic predisposition to gastric cancer. Combined with our previous report of germline hMLH1 mutations in two other subjects from this series, it is suggested that 2–3% of EOCG cases in North Americans may be owing to high-risk genetic mutations. These data should inform cancer geneticists on the utility of searching for specific genetic mutations in EOGC.